PERAN THE UNITED NATIONS MULTIDIMENSIONAL INTEGRATED STABILIZATION MISSION IN MALI (MINUSMA) DALAM PENYELESAIAN KONFLIK MALI - Jofi Pamungkas (HI 16 UMY 048, 2016)
*48 Conflict in Mali has made attention since its return in 2012 with the presence of rebellion and extremist groups in the North of Mali. The presence of these groups give threats and cause insecurity in the region. United Nations as an international organization has an obligation to build peace through its peacekeeping operations. United Nations through its peacekeeping operation in Mali named MINUSMA has a substantial role to give a hope upon Mali in finding a resolution to encounter the conflict. MINUSMA shall focus to ensure security, stabilization, and protection of citizens through the implementation of peace agreement. MINUSMA shall focus to support the national political dialogue and reconciliation through coordination and inclusive dialogue with the government and North parties. MINUSMA shall focus to support the re-establishment of state authority throughout the country, the rebuilding of the Malian security sector, the promotion and protection of human rights through restore the functions of public facilities, building coordination and military cooperation, monitoring and investigation to Human Rights.